Review on advances in structure–activity relationship, reaction & deactivation mechanism and rational improving design of selective catalytic reduction deNOx catalysts: Challenges and opportunities. (1st July 2023) - Chen, Junyan; Guan, Bin; Liu, Ziqian; Wu, Xingze; Guo, Jiangfeng; Zheng, Chunzheng; Zhou, Jiefei; Su, Tianxu; Han, Peicheng; Yang, Chuzhao; Zhang, Yaoyao; Qin, Bo; et al.
Highlights: The effects of Si/Al ratio and metal ions on zeolite catalysts are analyzed. The SCR properties of various types of zeolites are extensively discussed. Synergistic effects of hydrothermal aging and poisoning on catalysts are demonstrated. The mechanism of NH3 -SCR is illustrated deeply and comprehensively. The future of NH3 -SCR catalyst system is prospected strategically. Abstract: As NO x emissions are more strictly controlled, selective catalytic reduction of NOx by NH3 (NH3 -SCR), as one of the most efficient and stable technologies for deNO x, is widely used in the treatment of exhaust gases from diesel engines and thermal power plants. The development of highly active and stable NH3 -SCR catalysts is the key to improving the performance of NH3 -SCR. This paper systematically reviews the latest progress in the research of NH3 -SCR catalysts in various categories and their synergistic effects, including VO x -based catalysts, other metal oxide catalysts ranging from MnO x -based catalysts and CeO2 -based catalysts to Fe2 O3 -based catalysts and CuO-based catalysts, zeolite catalysts such as CHA-typed zeolite, oxysalt catalysts and MOFs catalysts. The mechanisms of hydrothermal aging and poisoning of NH3 -SCR catalysts and their synergistic effects, the mechanisms of NH3 -SCR reactions, and the mechanisms of N2 O generation are also reviewed. Faced with the requirements of higher NH3 -SCR activity and selectivity, wider temperature window, stronger hydrothermal aging and poisoning resistance of NH3 -SCR catalyst for the prospect of NOx net zero emission, this paper summarized three strategies: doping/modification, synthesis method improvement and support structure improvement, hoping to provide ideas for the innovative development of NH3 -SCR catalysts with better comprehensive performance and more application prospects.